The Impact of Social Media on Language Use Among Teenagers - Sefrianus Rianto; I Made Juliarta (Universitas Bali Dwipa, 2024)
The digital era, marked by rapid advancements in information and communication technology, has brought significant changes to various aspects of human life, including communication. Social media has become an integral part of teenagers' lives, influencing the way they interact, obtain information, and express themselves. This study aims to analyze the impact of social media on the changes in language use among teenagers. Using a qualitative research method, the study seeks to explore in-depth how social media shapes language use among teenagers. Through social media content analysis and in-depth interviews, the research finds that social media has triggered the emergence of slang, abbreviations, and unique emojis. This language use not only reflects teenagers' social identities but also affects their formal language skills. Additionally, social media influences the way teenagers think and communicate. Exposure to various types of texts and language styles on social media can enrich their vocabulary and improve their language skills. On the other hand, excessive exposure to inaccurate information or harsh language can negatively impact teenagers' critical thinking skills and their ability to evaluate information.